The Effect of Picture Series in Writing Narrative Text on Students’ Writing Ability at the 10th Grade of Mazro’atul Lughoh Islamic Boarding School Pare Kediri - Yasminto, Muhammad; Fifi Luthfiyah Maulidah (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2023)
This study was pre-experimental research design with one experimental group only. The target population of this study was all the tenth grade students of Mazro’atul Lughoh Islamic Boarding School Pare in the period of 2021/2022. The researcher took 26 students as the sample of the study, by using saturated sampling, because the population is relatively small. To collect data, the researcher used written pre-test and post-test in essay format, and the written assessment by Anderson. In analyzing the data, the researcher used IBM SPSS statistic versions. 20 application of paired sample t.test to know the difference between pre-test (before treatment) and post-test (after treatment). After collecting and calculating the data, the researcher found that mean score and the standard deviation of pre-test were 7.46 and 1.838, while the mean score of post-test was 16.15 and standard deviation was 2.781. In testing hypothesis, the researcher used t-test formula. The researcher found that t value was -16.183, Sig (2-tailed) = 0.00 < 0.05, at the level significance of df = 25. So, the null hypothesis was rejected and the alternative hypothesis could be accepted. It means that there was a significant difference between before and after given the treatment